Sildenafil citrate on retrobulbar and retinal circulation of rabbits - Amaral, Andréia Vitor Couto do; Silva, Germana Alegro da [UNESP]; Costa, Ana Paula Araújo; Coelho, Cássia Maria Molinaro [UNESP]; Renzo, Roberta [UNESP]; Laus, José Luiz [UNESP] (Universidade Federal de Santa Maria, 2014)
The effects of sildenafil on retrobulbar and retinal circulation were studied in 18 adult male, albino, homozygous rabbits, of the New Zealand White breed, randomly divided into 3 groups of 6 animals, for drug treatment at a dose of 3.5mg kg-1 every 24 hours, for 7, 15 and 30 days. Nine animals used for control were treated with saline solution at 0.9%. It was evaluated intraocular pressure (IOP), mean arterial pressure (MAP), ocular perfusion pressure (PPO), B-mode ultrasonography and fluorescein angiography before and at the end of treatments. A slight decrease in results of IOP, MAP and PPO after treatment with sildenafil was evident, however, there was no statistical significance. It was observed significant increased diameter of the ophthalmic artery after 7 and 30 days of treatment and decreased mean arterial pressure after 7, 15 and 30 days of treatment, with no statistical difference. On fluorescein angiography, it was observed that the arterial, arteriovenous and venous stages initiated more rapidly in animals after treatment, with significant difference on the arteriovenous stage at the 7th and 15th days. It was possible to admit that the sildenafil citrate improves blood circulation in the retina of rabbits, by increasing the speed of blood flow and decreasing the perfusion pressure.

Os efeitos do sildenafil sobre a circulação retrobulbar e a retiniana foram estudados em 18 coelhos machos adultos, albinos, homozigotos, da raça Nova Zelândia Branco, distribuídos aleatoriamente em 3 grupos de 6 animais, para tratamento com o fármaco na dose de 3,5mg kg-1 a cada 24 horas, por 7, 15 e 30 dias. Nove animais foram utilizados para controle, tratados com solução fisiológica a 0.9%. Foram avaliadas a pressão intraocular (PIO), a pressão arterial média (PAM) e a pressão de perfusão ocular (PPO), ultrassonografia em modo-B e a angiografia fluoresceínica, antes e ao término dos tratamentos. Evidenciou-se discreta diminuição nos resultados da PIO, da PAM e da PPO após tratamento com sildenafil, entretanto não houve significância estatística. Observou-se aumento significativo do diâmetro da artéria oftálmica após 7 e 30 dias de tratamento e diminuição da pressão arterial média após 7, 15 e 30 dias de tratamento, sem diferença estatística. À angiografia fluoresceínica, observou-se que as fases arterial, artério-venosa e venosa iniciaram-se mais rapidamente nos animais após o tratamento, com diferença significativa na fase artério-venosa ao 7o e 15o dias. Foi possível admitir que o citrato de sildenafil melhora a circulação de sangue na retina de coelhos, através do aumento da velocidade do fluxo de sangue e diminuição da pressão de perfusão.
Citrato de sildenafil sobre a circulação retrobulbar e retiniana de coelhos
Keywords: coelhos; citrato de sildenafil; circulação retrobulbar; circulação retiniana; ultrassonografia; angiografia fluoresceínica; rabbits; sildenafil citrate; retrobulbar circulation; retinal circulation; ultrasonography; fluorescein angiography